Factors influencing appearance and suitable habitat for wild elephants in the Khao Yai National Park, Thailand - YAMEERA NANLA; DOKRAK MAROD; PRATEEP DUENGKAE; PAANWARIS PAANSRI; JEDSADA NOOWONG; CHIRANAN MANITOEM; RONGLARP SUKMASUANG (Society for Indonesian Biodiversity, 2024)
Abstract. Nanla Y, Marod D, Duengkae P, Paansri P, Noowong J, Manitoem C, Sukmasuang R. 2024. Factors influencing appearance and suitable habitat for wild elephants in the Khao Yai National Park, Thailand. Biodiversitas 25: 3061-3072. Protected areas are designated to conserve biodiversity and provide a safe habitat for wildlife. This study aims to investigate the factors affecting elephant appearance and changes in habitat. The maxEnt program was used to analyze data derived from the patrolling system with constant quality monitoring. Four categories of environmental factors, climatic, physiological, biological, and anthropological factors were used to analyze the wild elephant data yearly from 2017 to 2022. The aim was to understand the effect of environmental factors on the wild elephants’ appearance and their habitat suitability. The results showed an average area under the receiver-operating-characteristic curve (AUC) was 0.81±0.004 SD. The results indicated that climatic (42.97%), physiological (32.62%), and anthropological (21.23%) factors affected the appearance of wild elephants significantly. Temperature factors showed the highest percentage contribution (39.04%), while water sources and salt licks, considered physiological factors, contributed 22.13% and 5.06%, respectively. Habitat suitability analysis revealed that the majority of the park area (64.91%) was categorized as unsuited and poorly suited habitat areas, while 35.07% was categorized as moderated and well-suited habitat areas for wild elephants. Implementing strategies to improve water sources and salt lick sites within the park and managing the area to minimize human disturbance both on the surrounding boundaries and the tourist destination sites are recommended to manage the wild elephant.